PEMBELAJARAN MATEMATIKA MENGGUNAKAN METODE GASING DI SDN INPRES SKOUW MABO - Hesti Maria Loisa Msiren; Agustinus Giay; Mickael Ruben Kaiway (JURNAL PENGABDIAN MANDIRI, 2025)
Education is means that people have to produce human resources that have a high quality and has the potential for global competitiveness. One of one of the educational contents in learning at various levels of education is mathematics. is the subject of Mathematics. . Mathematics is a subject that directs students to think logically, analytically, systematically, critically and creatively as well as the ability to solve life problems. According to (Shanty & Wijaya, 2012) The GASING method (GAmpang, aSyIk, menyenaNGkan) is a way of learning Mathematics initiated by Prof. Yohanes Surya. . Easy means that students are introduced using mathematical logic that is easy to remember. Fun means that students have a willingness to learn without coercion. And fun means that this leads to external factors where the use of props and games are used. Based on the description above, the Community Service Program is carried out to provide solutions to Calistung problems in students of SDN Inpres Skouw Mabo. The solution offered is learning by using the GASING Method, thereby making it possible for students to learn math more fun, enjoyable and active in developing thinking skills to the fullest so that it can improve student learning outcomes in mathematics in addition, subtraction and multiplication materials